Exploring medical undergraduates' perceptions of the educational value of a novel ENT iBook: a qualitative study. (2nd April 2016) - Al-Hussaini, Ali; Tomkinson, Alun
Abstract: Undergraduate otolaryngology exposure is limited. It may be consolidated by the use of an iBook as a self-study tool. Following invitation to participate by email, five focus groups were formed, each consisting of six medical students (18 female, 12 male, median age 23 years). The focus group transcripts were imported to the qualitative data analysis software NVivo (QSR International, UK). The iBook was found to have a clear and consistent presentation, and a focused and user-friendly style, with reasonable interactivity and a good range of well-integrated media elements. It was, overall, perceived to be a valuable educational resource by the medical students.